The tax statute of limitations - Lara Márquez, Jaime (2024)
An analysis is made of the statute of limitations in tax matters. An interpretative exercise is carried out on articles 43 and 44 of the Tax Code, in order to determine their true normative content. The central issues addressed are: (i) what is the beginning of the statute of limitations, also known as dies a quo, and (ii) what is the extension of the statute of limitations period. Regarding the first issue, it is argued that this does not occur on 1 January of the following year, as stated in case law and doctrine. It occurs much earlier, at the time prior to that referred to in Article 44 of the Tax Code at each of its initiations, such as the date on which the deadline for filing the annual tax return expires or on which the obligation becomes due. Regarding the second issue, it is argued that the total limitation period is not 4, 6 or 10 years, but that the limitation period is longer than that number of years, since the limitation period starts to run from the previous moment referred to in each of the subparagraphs of article 44 of the Tax Code.